Studies on redox and axial ligand properties of Meso-Mn(III) porphyrin by cyclic voltammetry and UV–Visible spectrophotometry. (2021) - Thandiayyakone, V.; Murugan, A.; Ravikumar, C.R.; Rajkumar, T.; Thillai Arasu, P.; Yadav, H.S.; Kotteeswaran, P.
Abstract: Manganese (III) complex with meso -5, 10, 15, 20-Tetrakis(2, 5-dimethoxy-phenyl) porphyrin, Mn[T(2, 5-(OCH3 )2 )PP], has been prepared utilizing meso -5, 10, 15, 20-Tetrakis(2, 5-dimethoxyphenyl)porphyrin, [T(2, 5-(OCH3 )2 )PP], and Manganese (II) acetate by complexation method. The prepared complex is characterized by UV–Vis spectrophotometric and cyclic voltammetric (CV) studies. The formation of Mn(III) porphyrin complex may be due to a significant metal-porphyrin π interaction. In Mn(III) porphyrin, Mn is in high spin d 4 configuration. The strongest σ bonding amongst the Mn and the porphyrin with four pyrrole nitrogen donors is responsible for the octahedral geometry. The change in geometry of the complex from octahedral to tetragonal is due to the presence of two axial amines supplied by the addition of secondary amine. Addition of primary amine leads to the formation of square pyramidal Mn(II) porphyrin, wherein the central metal atom is in high-spin d 5 configuration with the occupied d(x 2 -y 2 ) orbital whose orbital energy is low. This indicates that Mn(III) will be out of the plane of porphyrin. The change in the oxidation state of the central manganese atom and shape of the complex were supported by UV–Vis spectrophotometric studies. Cyclic voltammogram confirmed the oxidation and reduction behaviors of Mn porphyrin complex and the oxidation of Mn(III) into Mn(IV) at 0.3209 V.